Probabilistic Analysis of a Hospital Building Slab Foundation - Norbert Jendzelovsky; Katarina Tvrda (Applied Sciences, 2020)
This paper deals with the design of a five-storey hospital building, in which we focus on the deterministic and probabilistic analysis of its slab foundation. The hospital building bearing structure was modeled as a reinforced concrete skeleton. The Boussinesque model was selected for the subsoil under the plate foundation, which was a model of the elastic half-space, where properties of individual layers of the subsoil were entered according to the geological survey. The geological topology consisted of clay gravel and also included a layer of clay sand. In the stochastic solution, the variance of values was considered for individual mechanical properties of different types of soil. We analyzed the influence of the variance of input values on the resulting deflections, strain, and stress state of the plate foundation. Two variants of the solution were considered on the given numerical example. Probability calculations confirmed the probability of failure, which was allowed for the second limit state.